Efeitos imunológicos de dieta rica em sal na colite experimetal em camundongos - Sarah Leão Fiorini de Aguiar (2014)
Intestinal mucosa is the major surface of contact with the external environment. The gastrointestinal tract is in constant interaction with the microbiota and the antigens from diet. Under normal conditions, this interaction would induce oral tolerance, however, any failure in intestinal homeostasis result in inflammatory reactions. These manifestations include especially inflammatory bowel diseases (IBD) such as Crohn's disease (CD) and ulcerative colitis (UC). IBD results from a dysregulation of the balance among Treg cells and inflammatory Th1, Th2 and Th17 cells with reduction of regulatory activity of Tregs and/or overproduction of effector T cells. Recent studies have demonstrated an increased expression of Th17-related cytokines increased in both UC and CD. The diet has been long seen as a potential risk factor for the increased incidence of autoimmune diseases and IBD. A specific factor, which has been changing in the Western diet over time, is NaCl intake. Studies have demonstrated an increase in Th-17 cells in inflammatory diseases in the presence of small amounts of salt by the activation of SGK1 quinase. Thus, it is expected that the presence of salt in the diet of mice with colitis, would lead to an aggravation of inflammation. Our aim in this study was to test this possibility and to analyze the cellular mechanisms involved in the putative exacerbation of colitis induced by oral administration of 1% dextran sodium sulfate (DSS) in C57BL/6 mice. The high-salt diet led to worsening of colitis with increased clinical index, shortening of the colon, increased mieloperoxidase (MPO) production as well as altered cytokine profile and frequency of immune cells. Interestingly, administration of high salt diet alone was able to increase disease severity and IL-23 production in the colon. The same enhancing effect on DSS-induced colitis was observed with a diet rich in KCL, a salt that also induces SGK1. Thus, our results suggest that high-salt diets were capable of worsen colitis and this effect may be related to activation of SGK1.